Gramsci in Francia e la Francia di Gramsci - Sclocco, Camilla (International Gramsci Journal, 2023)
This is the abstract of a review in Italian by Camilla Sclocco of the two collectively-authored books Gramsci in Francia, edited by R. Descendre, F. Giasi and G. Vacca with the assistance of A. Crézégut, as part of the Gramsci nel mondo series, Bologna, il Mulino, 2020; and La France d’Antonio Gramsci, edited by R. Descendre e J-C. Zancarini and published by Ens Éditions, Lyon, 2021.